Manipulation of gene expression by infrared laser heat shock and its application to the study of tracheal development in Drosophila. Issue 3 (March 2015) - Miao, Guangxia; Hayashi, Shigeo; Trainor, Paul; Johnson, Randy
<x xml:space="preserve">Abstract</x> Background: Induction of gene expression in a specific cell and a defined time window is desirable to investigate gene function at the cellular level during morphogenesis. To achieve this, we attempted to introduce the infrared laser‐evoked gene operator system (IR‐LEGO, Kamei et al., 2009) in the Drosophila embryo. In this technique, infrared laser light illumination induces genes to be expressed under the control of heat shock promoters at the single cell level. Results: We applied IR‐LEGO to a transgenic fly stock, HS‐eGFP, in which the enhanced green fluorescent protein (eGFP) gene is placed under the control of heat shock protein 70 promoter, and showed that eGFP expression can be induced in single cells within 1–2 hr after IR illumination. Furthermore, induction of HS‐Branchless transgene encoding the Drosophila fibroblast growth factor (FGF) effectively altered the migration and branching patterns of the tracheal system. Conclusions: Our results indicated that IR‐LEGO is a promising choice for the timely control of gene expression in a small group of cells in the Drosophila embryo. By using IR‐LEGO, we further demonstrated that the tracheal terminal branching program is sensitive to localized expression of exogenous FGF. Developmental Dynamics 244:479–487, 2015. © 2014 Wiley Periodicals, Inc.